Environmental Health Surveillance of Household Drinking Water in Buluh Cina Village, a Riverine Rural Community along the Kampar River, Indonesia - Herniwanti Herniwanti; Oktavia Dewi; Emy Leonita; Rafni Nashabila; Rahmi Utamiasari (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Access to safe household drinking water remains a major environmental health concern in riverine rural communities that rely on untreated groundwater and refill water sources. Buluh Cina Village, located along the Kampar River in Riau Province, depends largely on shallow wells and refilled drinking water stations, many of which lack adequate disinfection and routine monitoring. This study aimed to conduct an integrated environmental health surveillance of household drinking water quality in Buluh Cina Village to identify microbiological and physicochemical risks relevant to local public health action. A cross-sectional surveillance study was conducted by collecting 30 water samples from points of access (supply) and 30 samples from points of use (ready-to-drink) in selected households using stratified random sampling. Laboratory analyses assessed microbiological parameters (Escherichia coli and Total Coliform), physical parameters (turbidity, color, and pH), and chemical parameters (iron, manganese, and residual chlorine), following the Indonesian Ministry of Health Regulation No. 2/2023. Overall, 91.7% of samples did not meet national drinking water quality standards. Microbiological contamination was detected at both sampling points, with Escherichia coli present in 33.3% of PA samples and 46.7% of PU samples, and total coliform contamination in 53.3% of PA samples and 63.3% of PU samples. However, the differences between PA and PU were not statistically significant. Residual chlorine was absent or below the recommended level in 70% of samples, while turbidity, abnormal pH, and elevated iron and manganese were also observed. These findings indicate significant environmental health risks associated with household drinking water in this riverine rural community. Priority public health actions include improving safe household water storage practices, increasing uptake of point-of-use disinfection, strengthening routine monitoring of refill drinking water depots, and integrating drinking water surveillance into primary health care center (puskesmas)-based environmental health workflows. This study provides locally grounded evidence to support targeted interventions for improving drinking water safety in riverine rural settings Keywords: Buluh Cina Village, Drinking Water Quality, Environmental Health Surveillance, Household Water Safety, Kampar River